Moral Integrity in African Political Leadership: A Philosophical Reflection on Ujamaa - Waitherero , Simon Njuguna (International Journal of Philosophy, 2023)
There is a tendency of defining various continental blocks under conventional views. The image of the African is of one desperately wanting to be heard. Trying to outdo himself to show that he actually belongs in the society of humankind, he would eagerly display his prowess in the fields of culture, of sport, of intellect and of civilization. All these efforts seem to meet with a rather listless audience who, it seems, will always require double evidence to doctor their credulity and would then give a complement more from courtesy than from solidarity. The African knows it. This being the case, the Africans leaders and their people in general need to liberate themselves from the chain. They must without option, seek the true freedom; Freedom from both the absolute mechanical coercion of physical force and the relative intellectually or moral coercion of a predetermined end. Freedom here does not mean not acting but a freedom that carries with it a responsibility, in all spheres of undertaking for the common good. This freedom of indifference is not a means to an end in itself. The good society is characterized by the absence of restraint in every walk of life. There is no such thing as the "perfect form of government" on earth, but any other form of government produces even less desirable results than democracy. Until today, no other form of government has been invented that could regulate public affairs better than democracy. Nyerere was trying to bring to his people an identity that was theirs but was lost in at a given point of time. Ujamaa was a call to the people of Tanzania to go back to their roots if they are to embark on anything. The family to the AFRICANS was an institution that was so much natural that its age to them was as old as the age of humanity. You cannot talk of the human person without touching directly or indirectly on the family. To this understanding, Nyerere called his people of Tanzania to embrace this noble call of Familyhood that helped them come together and stay together. This attitude was shared not only in Tanzania, but also in the Africa proper. Africa's family structure is alive and well. Retirement homes are rare because older people live with their families. Children are greatly valued. Extended family members take care of each other. Many African languages do not even have a word for "niece" or "nephew" because people regard the children of a sister or brother as practically their own children. Life in Africa involves the village, the tribe, the clan, the family. We see individuals and families demonstrate this spirit in every part of life. Not only in Tanzania, in Africa, the village, is the soul of life. We no doubt lack ideals in the present leadership in Africa. Dictators in Africa are under dictators (foreign masters). Morality and integrity, which acted as norms for African leadership are lost (most times, in the name of education and modernization).